Mazzinian Discipleship: Sara Nathan and Jessie White - Pasman, Ros (Spunti e Ricerche, 2016)
By the time of the death of Giuseppe Mazzini in March 1872, Italy was a united and independent nation but he was a defeated, disillusioned and disappointed revolutionary leader. The new Italy, a conservative monarchy, was far removed from his vision for a democratic, morally regenerated and virtuous republic based on the equality and participation of all its citizens, women as well as men: "Nessuno può ideare come la condizione morale dell’ltalia pesi sull’anima. Veder sorgere l’Italia servile, opportunista, cieca, immorale e peggio che non vederla sorgere."